1365. In Vitro Activity of Lefamulin (LEF) Against Bacterial Pathogens Causing Community-Acquired Bacterial Pneumonia (CABP): SENTRY Surveillance 2016 Results From Asia-Pacific (APAC) and Latin America (LA) - Paukner, Susanne (Open Forum Infect Dis, 2018)
BACKGROUND: LEF, a novel pleuromutilin antibiotic for IV and oral use, recently completed a phase 3 trial for the treatment of CABP in adults where it demonstrated noninferiority to moxifloxacin ± linezolid. LEF selectively inhibits bacterial translation. This study investigated the activity of LEF and comparators against contemporary bacterial respiratory pathogens collected from APAC and LA. METHODS: Unique isolates were collected from patients with pneumonia/respiratory (n = 551), blood stream (n = 169), skin and soft tissue (n = 244), and other (n = 55) infections in seven countries in APAC (n = 587) and four countries in LA (n = 432). LEF and comparators were tested by CLSI broth microdilution methods, and susceptibility was determined using CLSI (2018) breakpoints. RESULTS: In both APAC and LA, LEF showed potent in vitro activity against this collection of respiratory pathogens, with 100% of Streptococcus pneumoniae inhibited at ≤0.25 μg/mL. S. pneumoniae isolates were largely susceptible to moxifloxacin (98.2% APAC, 100.0% LA), amoxicillin/clavulanic acid (84.3% APAC, 89.4% LA), and ceftriaxone (85.2% APAC, 93.6% LA), but less susceptible to azithromycin (56.6% APAC, 68.1% LA) and penicillin (48.2% APAC, 67.0% LA). LEF was also active against Staphylococcus aureus with 99.6% of all isolates from both APAC and LA being inhibited at 0.25 µg/mL. 29.5% of methicillin-resistant S. aureus in APAC and 24.7% in LA showed particularly high resistance rates to erythromycin (59.3% APAC, 64.2% LA), moxifloxacin (49.4% APAC, 53.7% LA), and clindamycin (39.5% APAC, 59.7% LA). 98.2% and 97.9% of Haemophilus influenzae (in APAC and LA, respectively) were inhibited at LEF ≤2 μg/mL, and 100.0% of Moraxella catarrhalis were inhibited at LEF ≤0.12 μg/mL in both APAC and LA. Both organisms were largely susceptible to the comparators, except for ampicillin (49.1% and 74.5% susceptible among H. influenzae in APAC and LA, respectively) and trimethoprim/sulfamethoxazole (54.4% and 68.1% susceptible among H. influenzae) (figure). [Image: see text] CONCLUSION: In APAC and LA, LEF was highly active against pathogens collected from CABP patients in 2016, and its activity was not affected by resistance to other antibiotic classes. These data support the ongoing development of LEF for the treatment of CABP. DISCLOSURES: S. Paukner, Nabriva: Employee and Shareholder, Salary. R. K. Flamm, Nabriva Therapeutics: Research Contractor, Research support. S. P. Gelone, Nabriva Therapeutics: Employee, Equity, Shareholder and Salary. Achaogen: Shareholder, Equity, Shareholder. H. S. Sader, Nabriva Therapeutics: Research Contractor, Research support.